Striktur Uretra Berulang dengan Kejadian Penggunaan Kateter - Avicena Muhammad Archie (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: The urethral steak is a narrowing of the urethra due to scar tissue, leading to void obstruction dysfunction that has potentially serious consequences on the entire urinary tract. Urethral strictures can be caused by diagnostic and therapeutic urological procedures. This procedure is often used, in an aging population; therefore, urethral strictures may be able to occur more often. Purpose: Describes the relationship of repeated urethral strictures with the incidence of catheter use. Method: Using literature review studies. This article was created by summarizing the source of information obtained from 11 Indonesian and international articles and journals and one international website published in the period 2011-2021. Result: Urethral stricture is the time when the urethra tightens which results in a decrease or obstruction of urine flow that results in irritation and obstructive voiding symptoms. The use of catheters and other medical instruments for examination of the urinary tract that exceeds the diameter of the urethra can cause ischemia and internal trauma of the urinary tract. Conclusion: There is a relationship between recurrent urethral strictures and catheter use